Sigmoid Colectomy for Acute Diverticulitis in Immunosuppressed vs Immunocompetent Patients: Outcomes From the ACS-NSQIP Database. Issue 2 (February 2016) - Al-Khamis, Ahmed; Abou Khalil, Jad; Demian, Marie; Morin, Nancy; Vasilevsky, Carol-Ann; Gordon, Philip H.; Boutros, Marylise
Abstract : BACKGROUND: The management of acute diverticulitis in immunosuppressed patients is increasingly debated. The appropriate timing and type of operation remains controversial. OBJECTIVE: This study examines the impact of immunosuppression on mortality and morbidity following colectomies for diverticulitis in the emergency and elective settings. DESIGN SETTINGS: With the use of the American College of Surgeons National Surgical Quality Improvement Program database, the outcomes of immunosuppressed compared with immunocompetent patients who underwent colectomy for acute diverticulitis were compared. PATIENTS: The multi-institutional database was queried for patients who underwent colectomy for acute diverticulitis from 2005 to 2012. MAIN OUTCOMES MEASURES: The impact of immunosuppression on mortality, major morbidity, organ space infection, infectious complications, and wound dehiscence was assessed. RESULTS: Of 26, 987 patients, 1332 were immunosuppressed and 25, 655 were immunocompetent; 4271 patients had emergency (596 immunosuppressed and 3675 immunocompetent) and 22, 716 patients had elective (736 immunosuppressed and 21, 980 immunocompetent) colectomies for diverticulitis. In both groups, mortality and major morbidity were significantly higher in the emergency (immunosuppressed 16% and 45%, immunocompetent 4% and 28%) compared with the elective setting (immunosuppressed 2% and 25%, immunocompetent 0.4% and 12%), p < 0.001. On multivariate regression for the emergency setting, immunosuppression significantly increased mortality (OR, 1.79; 95% CI, 1.17–2.75) and did not significantly increase morbidity. On multivariate regression for the elective setting, mortality was similar in immunosuppressed and immunocompetent groups; however, major morbidity (OR, 1.46; 95% CI, 1.17–1.83) and wound dehiscence (OR, 2.69; 95% CI, 1.63–4.42) were significantly increased in immunosuppressed compared with immunocompetent patients. LIMITATIONS: The retrospective design and standardized outcomes are based on heterogeneous data. CONCLUSIONS: Emergency colectomy for diverticulitis is associated with higher mortality in immunosuppressed than in immunocompetent patients, whereas elective colectomy is associated with comparable mortality. In the elective setting, immunosuppressed compared with immunocompetent patients are at increased risk of major morbidity and wound dehiscence. Abstract : Supplemental Digital Content is available in the text.